Glutathione and Its Biosynthetic Intermediates Alleviate Cesium Stress in Arabidopsis - Adams, Eri; Miyazaki, Takae; Watanabe, Shunsuke; Ohkama-Ohtsu, Naoko; Seo, Mitsunori; Shin, Ryoung (Frontiers in Plant Science, 2020)
Phytoremediation is optimised when plants grow vigorously while accumulating the contaminant of interest. Here we show that sulphur supply alleviates aerial chlorosis and growth retardation caused by cesium stress without reducing cesium accumulation in Arabidopsis thaliana. This alleviation was not due to recovery of cesium-induced potassium decrease in plant tissues. Sulphur supply also alleviated sodium stress but not potassium deficiency stress. Cesium-induced root growth inhibition has previously been demonstrated as being mediated through jasmonate biosynthesis and signalling but it was found that sulphur supply did not decrease the levels of jasmonate accumulation or jasmonate-responsive transcripts. Instead, induction of a glutathione synthetase gene GSH2 and reduction of a phytochelatin synthase gene PCS1 as well as increased accumulation of glutathione and cysteine were observed in response to cesium. Exogenous application of glutathione or concomitant treatments of its biosynthetic intermediates indeed alleviated cesium stress. Interestingly, concomitant treatments of glutathione biosynthetic intermediates together with a glutathione biosynthesis inhibitor did not cancel the alleviatory effects against cesium suggesting the existence of a glutathione-independent pathway. Taken together, our findings demonstrate that plants exposed to cesium increase glutathione accumulation to alleviate the deleterious effects of cesium and that exogenous application of sulphur-containing compounds promotes this innate process.